Empirical Evidence on Human Trafficking and Migration-Debt Contracts in Bangladesh - Joarder, Munim; Miller, Paul (Routledge, 2014)
This article presents an analysis of the payments illegal migrants make to traffickers. It covers thetotal amounts of these payments, the incidence of migration-debt (or shared) contracts, and the value of the deferred payment component under these shared contracts. Data on illegal migrants from three field surveys conducted in Bangladesh from April 2009 to November 2010 are used. The results show that the total payments made to traffickers vary with easily observed characteristics (gender, age, marital status) but do not vary with details of the migration process (training provided, time spent in the trafficker’s queue). These relationships are consistent with exploitation. Migration-debt contracts are more prevalent when the costs of illegal migration arerelatively high, which adds empirical support to theoretical models such as Friebel and Guriev (2006). Contrary to existing reports, we document variations in fees for illegal passage across individuals.